Fostering Forensic Innovation - Julie Mennell (Measurement + Control, 2010)
Forensic science has a significant current and future role in crime detection, policing and the criminal justice system. Government and societal drivers, police priorities and advances in science and technology are demanding, as well as providing opportunities, for its impact and potential to be expanded, evaluated and assessed further. Within this, there is a need for the Criminal Justice System to be clear what it is looking for in respect of forensic science and to identify what the priorities, opportunities and processes are for development and possible expansion (of some areas, such as Digital Forensics, Biometrics and Imaging technologies). For example, if the police service's primary forensic science requirements are for reductions in unit costs, improvements in detection rates or faster turn-around times then this should be clearly specified to internal and external providers, while recognising that such requirements could have consequences for the development and delivery of forensic science, as well as policing, in other ways. A key area of agreement within the forensic community is the importance of establishing a vehicle for identifying future possibilities, potential and priorities which fosters innovation, maintains investment and shapes (rather than directs) the forensic science market; together with the need for engagement with the broader based academic community, in relation to research and development.